Noticing the Elephant in the Middle of the Room: Manifestation of Socio-Economic Inequalities in the World and Turkey - Lütfi Sunar; Merve Akkuş Güvendi (İnsan & Toplum)
Today the spotlights are over the problem of socio-economic inequalities. More people are having closeattention to this phenomenon in the world and in Turkey. Because the economic transformation experienced inthe last forty years triggers socio-economic inequalities to a great extent and creates different manifestations ofthe subject. Thus, the problem of socio-economic inequalities is subject to new research from different dimensions.Evaluation that monitoring inequalities through numerical indicators that give a general view, such as the ginicoefficient, are not fully explanatory about the case. Because the gini coefficient provides a one-dimensionalexplanation and mostly obscures the different dimensions of the inequality. For this reason, calculations that makeit possible to follow the contraction and expansion in different income groups within the country have started to bedeveloped. This difference in assessment stems from the need to provide a framework for both the income status ofdifferent social groups and the changing social balances. This paper focuses the changes and variations in differentincome groups such as top 1 percent, middle income group and poor people. This paper offers a new frameworkfor the assessment of socio-economic inequality by the analysis of the differentiation and change in these groups.